KERUSAKAN PERUMAHAN PERUMNAS DAN KPR-BTN DI TIPE TANAH ALUVIAL DAN REGOSOL OLER ORGANISME PERUSAK KAYU - Ginuk Sumarni; Agus Ismanto (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
This paper deals with a descriptive account on the infestation of wood destroying organisms on PERUMNAS and KPR-BTN houses on the alluvial and regosol soil types, Data were collected through interviews and questionaires.Results of the investigation reveal that the untreated red meranti wood group was severely attacked by termites and fungi after 7 years old. Mean while, the treated wood was also attacked by fungi after 14 years old. Untreated kamper wood was attacked by fungi after 5 years old. whereas the untreated. keruing wood was attacked by termites and fungi after 11 years old.